Preclinical Molecular PET-CT Imaging Targeting CDCP1 in Colorectal Cancer. (14th September 2021) - Cuda, Tahleesa J.; He, Yaowu; Kryza, Thomas; Khan, Tashbib; Tse, Brian W.; Sokolowski, Kamil A.; Liu, Cheng; Lyons, Nicholas; Gough, Madeline; Snell, Cameron E.; Wyld, David K.; Rose, Stephen; et al.
Abstract : Colorectal cancer (CRC) is the third most common malignancy in the world, with 22% of patients presenting with metastatic disease and a further 50% destined to develop metastasis. Molecular imaging uses antigen-specific ligands conjugated to radionuclides to detect and characterise primary cancer and metastases. Expression of the cell surface protein CDCP1 is increased in CRC, and here we sought to assess whether it is a suitable molecular imaging target for the detection of this cancer. CDCP1 expression was assessed in CRC cell lines and a patient-derived xenograft to identify models suitable for evaluation of radio-labelled 10D7, a CDCP1-targeted, high-affinity monoclonal antibody, for preclinical molecular imaging. Positron emission tomography-computed tomography was used to compare zirconium-89 ( 89 Zr)-10D7 avidity to a nonspecific, isotype control 89 Zr-labelled IgG κ 1 antibody. The specificity of CDCP1-avidity was further confirmed using CDCP1 silencing and blocking models. Our data indicate high avidity and specificity for of 89 Zr-10D7 in CDCP1 expressing tumors at. Significantly higher levels than normal organs and blood, with greatest tumor avidity observed at late imaging time points. Furthermore, relatively high avidity is detected in high CDCP1 expressing tumors, with reduced avidity where CDCP1 expression was knocked down or blocked. The study supports CDCP1 as a molecular imaging target for CRC in preclinical PET-CT models using the radioligand 89 Zr-10D7.